Radiation resistance of a cyjindrical antenna immersed in a weakly ionized magnetoplasma. II - Shukla P.K.; Singh K.P. (My University, 2025)
The field components for electromagnetic and eletromagnetic waves from a cylindrical antenna radiating in a weakly ionized magnetoplasma and expressions for radiation resistances assuming sinusoidal current distribution in the antenna have been obtained. The effect of a steady magnetic field on the radiation resistances has been discussed. it has been concluded that the magnetic field changes considerably the radiation characteristics of an antenna. © 1972, Taylor & Francis Group, LLC.